Controlling banana bunchy top disease in Benin: Crop protection strategies with socio‐economic perspectives - Retkute, Renata; Zandjanakou‐Tachin, Martine; Omondi, Bonaventure Aman; Agoi, Ulrich Roland; Vodounou, Yaovi Marc; Akofodji, Hermine; Akpla, Evrard; Dossou, Laurence; Médénou, Emiline; Etchiha, Alban; Attadéou, Alphonse; Kumar, P. Lava; et al. (Wiley, 2025)
Societal Impact Statement Banana and plantain are vital for food security and income in West Africa, yet banana bunchy top virus (BBTV) threatens production. This study combined remote sensing, field surveys, modelling and socio‐economic analysis to assess BBTV spread and control strategies in Benin. We found that risk is highest in southern regions with low disease awareness, limited adoption of control measures and widespread informal planting material exchange. By identifying priority areas and context‐specific interventions, our findings provide actionable guidance for targeted BBTV management, supporting smallholder resilience, reducing disease impact and safeguarding livelihoods across sub‐Saharan Africa. Summary This study investigates banana bunchy top virus (BBTV), a major threat to banana and plantain production in Benin, which are critical for food security and income for smallholder farmers. We combined remote sensing, field surveillance, household surveys and mathematical modelling to map banana cultivation; detect BBTV prevalence; and evaluate control strategies. BBTV was detected in 140 of 747 fields, with the highest prevalence in southern humid regions; modelling showed that injection was the most effective nationally, while uprooting was the most effective in high‐risk, socio‐economically vulnerable areas. Our findings highlight the need for context‐specific, spatially targeted interventions integrating clean planting materials, farmer education and epidemiologically informed management to enhance smallholder resilience and safeguard livelihoods.